The counts of Tripoli and Lebanon in the twelfth century sons of Saint-Gilles - Lewis, Kevin James 1987- (Routledge, Taylor & Francis Group, 2017)
"What little has been written previously on the Lebanese 'crusader' county of Tripoli has focused upon the southern French ancestry of the counts of Tripoli, descendants of the counts of Saint-Gilles. Kevin Lewis argues for a deeper understanding of the processes that shaped the county throughout the twelfth century. What emerges is an intriguing analysis of how the counts struggled to exert their power over Lebanon in the face of insurmountable geographical forces and a great diversity of religions, languages and cultures. This book challenges prevailing knowledge of this little-known crusader state and the medieval Middle East as a whole"...Provided by publisher